Designing an Exercise Protocol to Improve Impulsivity Control in Children With Attention Deficit Hyperactivity Disorder: A Pilot Study - Behzad Amini; Seyed Ali Hosseini; Ebrahim Pishyareh; Enayatollah Bakhshi; Hojjat Allah Haghgoo (Journal of Rehabilitation)
Objective Impulsivity, as one of the early diagnostic indicators of attention deficit hyperactivity disorder, appears in childhood through movement. Decreasing impulsive behavior and increasing emotional-motor control over this disorder have been the focus of researchers and clinical experts. Inhibition deficiency is considered the root cause of impulsivity, leading to a deficit of impulsivity control and response control disorder. Materials & Methods Based on the hypothesis of an inhibition deficiency, leading to disruptions in three areas of executive functioning, namely behavioral control, cognitive flexibility, and working memory, impulsivity control, and response control disorder are at the center of attention deficit hyperactivity disorder (ADHD) symptoms. This study designs a specific exercise package, including physical exercises in the form of rhythmic movements in the dual-task paradigm along with cognitive exercises in a step-by-step and difficulty level, considering the child’s interests, capabilities, and freedom of choice. The type of exercise at each level and its effect on improving impulsivity control in these individuals have been investigated. Results The results indicated the possibility of performing the exercises in dual tasks and the high acceptance of gradual difficulty in performing the exercises of this package. The preliminary analysis of the study shows the relative improvement of the indices of attention, caution and response control in each of the individual participants separately. Conclusion The combination of exercises in the protocol, including rhythmic and providing optional settings adding companionship therapists in the form of therapeutic relation led to feasibility. The results in the field of improving the infrastructure of impulsivity control can be promising and worthy of consideration; however, conducting research with a larger number of participants and examining the results compared to the control group can be the basis for extensive research in this field.